ΣΩΤΗΡΗΣ ΠΑΡΑΣΧΑΣ: Georgia Gotsi και Despina Provata (επιμ.), Languages, Identities and Cultural Transfers: Modern Greeks in the European Press (1850-1900), Άμστερνταμ, Amsterdam University Press, 2021, 270 σελίδες. (Σύγκριση/Comparaison/Comparison, 2022)
Βιβλιοκρισία του βιβλίου: Georgia Gotsi και Despina Provata (επιμ.), Languages, Identities and Cultural Transfers: Modern Greeks in the European Press (1850-1900), Άμστερνταμ, Amsterdam University Press, 2021, 270 σελίδες.